The Economic Behavior of Paddy Farm Household in Suboptimal Land (Case in Pemulutan Area, Ogan Ilir Regency, South Sumatera Province) - Laila Husin (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
This study aims to analyze the determinant factors of paddy farm household’s economic behavior, specifically influence the productive activities, that is paddy production and income, family labor allocation and farm household expenditure to achieve their family’s food security. This research used cross section data, where 90 paddy farm households (3 villages) as sample in Pemulutan area, Ogan Ilir Regency, South Sumatera Province, and analyzed by descriptive and econometric tecnics. The estimation of econometric model (the simultaneous equations) used two stages least squares (2SLS) method. The result of this study showed that most respondents have some income sources (from paddy farm, non-paddy farm and off farm activities). The average paddy production is relatively low (3.937 tons/ha), the average tillage paddy area is around one hectare and the dried paddy price around Rp 3 to 3.8 thousands per kg. This paddy farm is the main source income (Rp9,844,509 or around US 871 per hectare per year ). The other income sources from non paddy farm income (Rp662,560), off farm income (Rp328,389) and non working earning (Rp169,444). On average, the total family income (Rp14,304,898 per year) was higher than total family expenditure (Rp12,47,427), where for food is Rp9,156,394 (68.21%) is higher than for non food consumption is Rp3,691,033 (31.79 %), thus the paddy farm household in this area can make saving around Rp1,453,581 (9.70% from total family income). The highest farm household time allocation is for paddy farming activity (around 50.00 %). The behavior of farm household working time is affected by faddy farm land area, paddy farm income, non farm income and farmer’s age. The behavior of household production is influenced by farm land area, the allocation of family labor on the paddy farm and the cost of paddy farming. The behavior of household consumption is affected by total household income and the number of household member. These paddy farm household behavior as adaptation to the climate change in this area, however they still can achieve their food security through fulfilling their primary needs